2010
DOI: 10.1002/bmc.1391
|View full text |Cite
|
Sign up to set email alerts
|

Validated method for bioactive lignans in Schisandra chinensis in vitro cultures using a solid phase extraction and a monolithic column application

Abstract: A simple and rapid method for determination of six lignans found in plant cell cultures of Schisandra chinensis was developed and validated. The lignans were extracted from plant samples with methanol and the extracts were effectively cleaned by solid-phase extraction using Strata C18-E (Phenomenex) cartridges. Chromatographic separation was carried out on a Chromolith Performance RP-18e monolithic column (100 x 4.6 mm, Merck) using an isocratic mobile phase of acetonitrile and water in a 50:50 (v/v) ratio. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Besides examining SchS raw materials for SL content, the current study involved establishing in vitro shoot cultures of the Sadova cultivar, with the aim of providing an alternative, sustainable source of the aforementioned compounds. So far, there have been only few reports on in vitro cultures of Sch, including the projects of the authors of this paper (Březinová et al 2010 ; Kohda et al 2012 ; Szopa and Ekiert 2012 ; Szopa et al 2016b ), whereas in vitro cultures of SchS has not been studied at all.…”
Section: Discussionmentioning
confidence: 93%
“…Besides examining SchS raw materials for SL content, the current study involved establishing in vitro shoot cultures of the Sadova cultivar, with the aim of providing an alternative, sustainable source of the aforementioned compounds. So far, there have been only few reports on in vitro cultures of Sch, including the projects of the authors of this paper (Březinová et al 2010 ; Kohda et al 2012 ; Szopa and Ekiert 2012 ; Szopa et al 2016b ), whereas in vitro cultures of SchS has not been studied at all.…”
Section: Discussionmentioning
confidence: 93%
“…13.90 mg/100 g DW), gomisin A (11.90 mg/100 g DW), and schisandrin (max. 0.90 mg/100 g DW) (Březinová et al 2010). The presence of deoxyschisandrin, gomisin G, schisantherin A, schisandrin C, schisantherin B, and schisanthenol, and other tentatively identified dibenzocyclooctadiene lignans, which were detected under our study in significant quantities, had not been revealed by Březinová’s team.…”
Section: Discussionmentioning
confidence: 99%
“…A much broader scope of research is presented by the second work by scientific workers from Masaryk and Mendel Universities in Brno (Březinová et al 2010). In their study different cell lines were examined; three lines of embryogenic callus in agar cultures were maintained in the dark (lines: LA-4, LAT-52, LA-58) and five lines of suspension cultures were maintained in a photoperiod (lines: LA-1, LA-4, LA-10, LAT-52, LA-58).…”
Section: Biotechnological Studiesmentioning
confidence: 99%